Plant and method for the production of metal products - BOBIG PAOLO; BENEDETTI GIANPIETRO (2016)
Plant for the production of metal products comprising: - a main rolling line (12) configured to roll thin slabs; - a main casting line (11) of thin slabs associated downstream to a heating and/or maintenance furnace (18) to heat and/or maintain the cast thin slabs at a uniform temperature, the main casting line (11) being positioned upstream of and aligned with said main rolling line (12), the main rolling line (12) being configured to roll the thin slabs arriving at least from the heating and/or maintenance furnace (18); - an auxiliary rolling line (22) provided with at least one rolling unit (24) configured to roll conventional slabs and obtain thin slabs, and with a transfer unit (25) positioned downstream of the rolling unit (24) and configured to transfer the thin slabs rolled by the latter to the heating and/or maintenance furnace (18). 用于生产金属制品的设备，包括：主轧制生产线(12)，其构造成轧制薄板坯；薄板坯的主铸造生产线(11)，其下游关联至加热和/或保持熔炉(18)而加热所铸造的薄板坯和/或将所铸造的薄板坯保持于均等温度，所述主铸造生产线(11)位于所述主轧制生产线(12)的上游并与所述主轧制生产线对齐，所述主轧制生产线(12)构造成轧制至少来自所述加热和/或